LKPD Berbasis Project Based Learning Konteks Lingkungan Sekolah untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IV SD - Ariska, Nova; Susanta, Agus; Juarsa, Osa (UNIB Press, 2024)
The aims of this study are develop Project Based Learning (PJBL) based LKPD on pictograms and bar diagrams for class IV elementary schools. The design of this study was development research using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The data collected is quantitative and qualitative data. Data collection uses observation methods, structured interviews, questionnaires and tests. The data analysis technique used in this study was qualitative descriptive analysis and quantitative descriptive analysis techniques. The results of this study show that (a) the results of the material content expert's review were very good with a percentage of 85% (b) the results of the linguist's review were very good with a percentage of 86% (c) the results of the design expert's review were very good with a percentage of 84%. (d) the results of teacher and student responses were very good with a percentage of 92% teacher responses and 91% student responses. The average N-Gain value for the experimental class is 66%, which means it is effective in improving student learning outcomes. So the conclusion of this research is that PJBL-based LKPD in the context of the school environment is suitable for use, has a very good response and can improve student learning outcomes.